Kepailitan Perseroan Perorangan dalam Undang-Undang Cipta Kerja - Gloria, Monica (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2021)
The times in the economic sector in fact encourage a country to try to provide regulations in accordance with global demands. One of them is done by Indonesia by using the Omnibus Law system, then regulating a new legal entity, namely an Individual Company. The application of this legal entity aims to encourage Micro and Small Businesses to be more developed, so that by turning them into legal entities, business owners will find it easier to get investment from banks and manage the company more regularly. However, in the event that the individual company bankruptcy application has not been regulated in the Cipta Kerja act or its implementing regulations, the purpose of this study is to see how the bankruptcy process of an Individual Company in Indonesia, using the normative juridical method, which looks at statue approach and conseptual approach.